Utilization of Information and Communication Technology To Strengthen Islamic Sharia through Islamic Education in Aceh - Muhammad Fazil; Syukur Kholil; Suwardi Lubis (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Researching Islamic education differences, notably in Aceh, aims to understand, solve, and benefit from millennial-era Islamic education issues. From elementary to high school, the Aceh government is committed to improving Islamic education. This material aims to create an intelligent, committed, and religious Acehnese generation.This research focuses on using ICT to improve Islamic Sharia in Aceh through Islamic education. Qualitative research explains, describes, and analyzes research results using interviews and observations with respondents and informants. February–September 2020 was the research period. This method was used to assess Islamic education in Aceh when Islamic law was implemented. To understand this topic, one must consult different sources. Data includes curriculum, books, journals, research reports, laws, encyclopedias, articles, newspapers, etc.Electronic communication is a new learning tool. Communication is the most important component of learning. Everyone has several IT alternatives today. Islamic religious educators are no exception. E-dukasinet/internet-based learning, telematics, e-learning, blogs, multimedia resource centers, comic-based learning, and video conferencing. Examples of technology in Islamic education include: Audio, visual, visual-audio, and Internet-based technologies.Remote/online learning is usually defined as education using ICT. Educational institutions' efforts to provide distance learning illustrate this. Computers provide print and electronic teaching materials for this educational transition. Aceh Islamic education uses ICT to uphold Islamic law.